The Role of the Armenian Apostolic Church in the Lebanese-Armenian Identity Formation - Kendirjian, Karnie (2022)
Research on migration studies has been mostly aimed to understand diasporic communities and their identity. Abundant research has been conducted to explore the various factors contributing to the Armenian identity preservation in Lebanon. Karnie Kendirjian’s thesis titled “The Role of the Armenian Apostolic Church in the Lebanese-Armenian Identity Formation” aims to examine the hybrid identities of diasporic communities. As it takes the Armenian diasporic community in Lebanon as a case study, this thesis focuses on the role of the Armenian Apostolic Church in the Lebanese-Armenian identity formation. The analysis is based on thorough literature review and key informant interviews. This thesis contends that the Armenian Apostolic Church, with its cultural and political objectives, is the fundamental factor behind the Lebanese-Armenian identity formation.